Penilaian Kualitas Air Dari Mata Air Sebagai Sumber Air Baku Untuk Air Minum Di Kecamatan Singosari Kabupaten Malang - Siswoyo, Hari; Haribowo, Riyanto; Prabandari, Ni Luh Putri; Permata, Veronika Yulia; Kurniawan, Joko (Universitas Kristen Maranatha, 2024)
Some residents in the Singosari District, Malang Regency use the potential of springs as raw water for drinking water. One of the main aspects that must be considered in exploiting the potential of springs is the feasibility of the quality of the water. The quality of the water used by residents is not necessarily identified. This research was carried out with the aim of providing an assessment of the feasibility of water quality from springs as a source of raw water for drinking water. The object of this research was 12 springs spread across the Singosari District. Physico-chemical parameters used as the basis for assessing water quality include pH, TDS, nitrate (NO3–), turbidity, iron (Fe), chloride (Cl–), manganese (Mn), sulfate (SO42–), ammonia (NH3), and sodium (Na+). The water quality from springs is assessed by using a water quality index model. The water quality index value of the springs studied has a range of 8.80 – 41.13. There are 10 springs with very good water quality category and 2 springs with good water quality category.